Thermal stability of polyoxometalate compound of Keggin K8[2-SiW11O39]∙nH2O supported with SiO2 - Yunita Sari M A; Maria Danesti Situngkir (Science and Technology Indonesia, 2016)
Synthesis through sol-gel method and characterization of polyoxometalate compound of K8[b2-SiW11O39]∙nH2O supported with SiO2 have been done. The functional groups of polyoxometalate compound was characterized by FT-IR spectrophotometer for the fungtional groups and the degree’s of crystalinity using XRD. The acidity of K8[b2-SiW11O39]∙nH2O/SiO2 was determined qualitative analysis using ammonia and pyridine adsorption and the quantitative analysis using potentiometric titration method. The results of FT-IR spectrum of K8[b2-SiW11O39]∙nH2O appeared at wavenumber 987.55 cm-1 (W=O), 864.11 cm-1 (W-Oe-W), 756.1 cm-1 (W-Oc-W), 3425.58 cm-1 (O-H), respectively and spectrum of K8[b2-SiW11O39]SiO2 appeared at wavenumber 956.69 cm-1 (W=O), 864.11 cm-1 (W-Oe-W), 3448.72 cm-1 (O-H), respectively. The diffraction of XRD pattern of K8[b2-SiW11O39]∙nH2O and K8[b2-SiW11O39]∙nH2O/SiO2 compounds show high crystalinity. The acidic properties showed K8[b2-SiW11O39]∙nH2O/SiO2 more acidic compared to K8[b2-The SiW11O39]∙nH2O. The qualitative analysis showed pyridine compound adsorbed more of polyoxometalate compound of K8[b2-SiW11O39]∙nH2O/SiO2. Analysis of stability showed that the K8[b2-SiW11O39]∙nH2O/SiO2 at temperature 500°C has structural changes compare to 200-400oC which was indicated from vibration at wavenumber 800-1000 cm-1. Keywords : K8[b2-SiW11O39]∙nH2O, polyoxometalate, SiO2.